Inherited 2q23.1 microdeletions involving the MBD5 locus. Issue 5 (8th August 2017) - Tadros, Shereen; Wang, Rubin; Waters, Jonathan J.; Waterman, Christine; Collins, Amanda L.; Collinson, Morag N.; Ahn, Joo W.; Josifova, Dragana; Chetan, Ravi; Kumar, Ajith
Abstract: Background: Microdeletions of 2q23.1 disrupting MBD5 and loss of function mutations of MBD5 cause MBD5‐ Associated Neurodevelopmental disorders (MAND). Nearly all reported patients have been isolated cases of de novo origin. Methods: This study investigates three families with inherited MBD5 mutations from three different Regional Genetics Centres in the UK. Results: Two of the parents in the study had MBD5 deletions in a mosaic form. The parent with an MBD5 deletion in an apparently nonmosaic form has a psychiatric disorder in the absence of developmental delay or dysmorphism. Conclusions: Inherited forms of MBD5 deletions are rare, but do occur, especially in a mosaic form. The phenotypic spectrum of MAND may be wider than previously thought. Abstract : This report describes three families with inherited 2q23.1 microdeletions including a parent who has the deletion in an apparently nonmosaic form and has mental health issues in the absence of developmental delay or dysmorphic features. We also report two instances of parental mosaicism, which could be significant for counseling parents of an affected child with an apparent de novo deletion.